FAM83A Promotes Lung Cancer Progression by Regulating the Wnt and Hippo Signaling Pathways and Indicates Poor Prognosis - Zheng, Yi-Wen; Li, Zhi-Han; Lei, Lei; Liu, Chen-Chen; Wang, Zhao; Fei, Liang-Ru; Yang, Mai-Qing; Huang, Wen-Jing; Xu, Hong-Tao (Frontiers in Oncology, 2020)
FAM83A (Family with sequence similarity 83, member A) was found highly expressed in cancers. The purpose of this study was to clarify the role and mechanism of FAM83A in lung cancers. The expression of FAM83A in lung cancer cells was enhanced by gene transfection or knocked-down by small interfering RNA interference. The key proteins of the Wnt signaling pathway, the Hippo signaling pathway and epithelial-mesenchymal transition (EMT) were examined using western blot. The proliferation and invasion of lung cancer cells was examined using cell proliferation, colony formation, and invasion assays. The expression of FAM83A in lung cancer tissues was significantly increased and was correlated with advanced TNM stage and poor prognosis. Overexpression of FAM83A enhanced the proliferation, colony formation, and invasion of lung cancer cells. Meanwhile, FAM83A overexpression increased the expression of active-β-catenin and Wnt target genes, and the activity of EMT. Furthermore, in FAM83A-overexpressed cells, the activity of Hippo pathway was down-regulated, while the expression of YAP and its downstream targets cyclin E and CTGF were up-regulated. The inhibitor of the Wnt signaling pathway, XAV-939, reversed the promoting effect of FAM83A on YAP, cyclin E, and CTGF. On knocking-down the expression of FAM83A, we obtained the opposite results. However, the inhibitor of GSK3β, CHIR-99021, restored the expression of YAP, cyclin E and CTGF after FAM83A was knocked down. FAM83A is highly expressed in lung cancers and correlated with advanced TNM stage and poor prognosis. FAM83A promotes the proliferation and invasion of lung cancer cells by regulating the Wnt and Hippo signaling pathways and EMT process.